Effects of ciprofol on respiratory-related adverse incidence in patients with obesity during painless gastroscopy: a prospective, randomized clinical trial - Yanjing Zhang; Danru Xie; Feifei Li; Mengjiao Che; Yaoheng Yang; Geng Li; Yiwen Zhang (Perioperative Medicine)
Abstract Background Ciprofol is an intravenous anesthetic agent which in low doses produces sedation. It was developed via structural modification of propofol. Ciprofol is claimed to reduce respiratory depression. The object of the present study was to investigate whether or not ciprofol did actually reduce respiratory depression or not in patients with obesity undergoing gastroscopy. Methods A total of 84 patients with obesity scheduled for gastroscopy were enrolled. The participants were randomly allocated to receive sedation with ciprofol (group C) or propofol (group P). The primary outcome was the incidence of respiratory-related adverse events (AEs), whereas the secondary outcomes were the incidence of further intraoperative and postoperative AEs; procedure and anesthesia success rates; Narcotrend index (NI); induction dosage; procedure time; recovery time; discharge time; and satisfaction ratings from the patients, anesthesiologists, and endoscopists. Results The incidence of respiratory-related AEs was significantly lower in group C than in group P (17.5% vs. 57.5%; P < 0.001). The occurrence of hypotension and movement during procedural events in group C was markedly reduced compared with that in group P (P = 0.024 and 0.007, respectively). No notable differences were observed in the occurrence of additional AEs or in the success rates of the procedure and anesthesia between the two groups (P > 0.05). The three-point satisfaction levels were comparable between the groups (P > 0.05). Conclusions 0.4 mg/kg of ciprofol provides anesthesia comparable with 2.0 mg/kg of propofol. However, it is related to reduced respiratory-related AEs and hypotension during gastroscopy in patients with obesity; thus, ciprofol is preferred to propofol for anesthesia in obese patients. Trial registration This study was registered in the Chinese Clinical Trial Registry (KYLS20230625; first registration date: 29/06/2023).